Mixed magnetohydrodynamic convection in a Cu-water-nanofluid-filled ventilated square cavity using the Taguchi method: A numerical investigation and optimization - Shirvan, Kamel Milani; Öztop, Hakan Fehmi; Al-Salem, Khaled (Springer Heidelberg, 2017)
In this paper, the optimal condition of mixed magnetohydrodynamic convection in a ventilated square cavity filled with a Cu-water nanofluid with different positions of inlet and outlet port is analyzed. To serve the purpose, the L16 (4(3)) orthogonal Taguchi array is used by means of the Taguchi method. Discretization of the governing equations is obtained through the finite volume method and then solved with the SIMPLE algorithm. A very effective mode, namely the Taguchi method, is used for the L16 (4(3)) orthogonal Taguchi array. The effects of Richardson number (0.01-10), Hartmann number (0-50), and inlet and outlet positions (0-0.9 H) at Phi = 1% are investigated. The entire analysis is performed for fixed Grashof number 10(4). It is found that the mean Nusselt number decreases by increasing the Richardson number, Hartmann number and the position of the inlet port, whereas the position of the outlet port has an increment effect on the mean Nusselt number. The optimal distance of outlet port position from the upper wall of the cavity is 0.9H at Richardson number 0.01, while the Hartmann number of optimal design for heat transfer is noted as 30. Comparison with existing studies is made as a limiting case of the considered problem.
Keywords: Lid-Driven Cavity; Mhd Natural-Convection; Heat-Transfer; Magnetic-Field; Entropy Generation; Al2O3-Water Nanofluid; Flow; Fluid